Nanoscale periodic distribution of energy dissipation at the shear band plane in a Zr-based metallic glass. (May 2021) - Wang, D.P.; Zhang, H.T.; Guo, P.Y.; Sun, B.A.; Wang, Y.X.
Abstract: The local energy dissipation near the shear band plane was characterized by using a method of amplitude-modulation atomic force microscope, in a Cu50 Zr50 metallic glass. The shear band plane has higher energy dissipation than the undeformed metallic glass surface. Along the propagating direction of shear bands, the energy dissipation is periodically distributed, arising from density changes and discontinuous growth of the shear offset during the sliding process. Our experimental findings of the fluctuated distribution of energy dissipation at the plane uncover some dynamic information about the shear banding process and explain some key features of shear bands in metallic glasses. Graphical abstract: Image, graphical abstract